2017
DOI: 10.1016/j.scib.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast epitaxial growth of metre-sized single-crystal graphene on industrial Cu foil

Abstract: A foundation of the modern technology that uses single-crystal silicon has been the growth of high-quality single-crystal Si ingots with diameters up to 12 inches or larger. For many applications of graphene, large-area high-quality (ideally of single-crystal) material will be enabling. Since the first growth on copper foil a decade ago, inch-sized single-crystal graphene has been achieved. We present here the growth, in 20 minutes, of a graphene film of 5 50 cm 2 dimension with > 99% ultra-highly oriented gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
349
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 507 publications
(365 citation statements)
references
References 34 publications
8
349
0
1
Order By: Relevance
“…Figure c shows the Raman spectrum of the transferred graphene on top of the grating. The graphene used in this work is grown by chemical vapor deposition (CVD) method . The G and 2D peaks of the Raman shift are located at 1582 cm −1 and 2668 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure c shows the Raman spectrum of the transferred graphene on top of the grating. The graphene used in this work is grown by chemical vapor deposition (CVD) method . The G and 2D peaks of the Raman shift are located at 1582 cm −1 and 2668 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Many efforts have demonstrated that the pretreatment of the substrates (such as long‐time annealing, polishing, resolidification, etc.) can effectively decrease the number of active sites . However, these methods have some weaknesses.…”
Section: Vapor‐phase Growth Of High‐quality Wafer‐scale 2d Materialsmentioning
confidence: 99%
“…A straightforward route is to grow up from a single seed, which is similar to silicon ingot growth . Another thoroughgoing approach is to make the multinucleation domains with identical orientation seamless coalesce into a wafer‐scale single‐crystal film, which can usually be achieved on a single‐crystal substrate or liquid substrate . The third effective one is the evolutionary selection growth (ESG) that can eliminate the formation of undesired seeds to get large‐area single‐crystal 2D materials, even on a polycrystalline substrate .…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress has been made in 2D crystal growth [1][2][3], and monolayer graphene crystals beyond the cm-scale [4] and continuous films over areas just limited by the growth reactor geometry [5][6][7] are now routinely achieved by chemical vapour deposition (CVD). The graphene CVD process utilises a catalytic substrate to achieve high crystallinity [2,[8][9][10] and for the majority of emerging applications the graphene has to be released from this parent growth substrate and transferred into the device stack.…”
Section: Introductionmentioning
confidence: 99%